A European benchmarking system to evaluate in-hospital mortality rates in acute coronary syndrome: The EURHOBOP project. (1st March 2015) - Dégano, Irene R.; Subirana, Isaac; Torre, Marina; Grau, María; Vila, Joan; Fusco, Danilo; Kirchberger, Inge; Ferrières, Jean; Malmivaara, Antti; Azevedo, Ana; Meisinger, Christa; Bongard, Vanina; et al.
Abstract: Background: Hospital performance models in acute myocardial infarction (AMI) are useful to assess patient management. While models are available for individual countries, mainly US, cross-European performance models are lacking. Thus, we aimed to develop a system to benchmark European hospitals in AMI and percutaneous coronary intervention (PCI), based on predicted in-hospital mortality. Methods and results: We used the EURopean HOspital Benchmarking by Outcomes in ACS Processes (EURHOBOP) cohort to develop the models, which included 11, 631 AMI patients and 8276 acute coronary syndrome (ACS) patients who underwent PCI. Models were validated with a cohort of 55, 955 European ACS patients. Multilevel logistic regression was used to predict in-hospital mortality in European hospitals for AMI and PCI. Administrative and clinical models were constructed with patient- and hospital-level covariates, as well as hospital- and country-based random effects. Internal cross-validation and external validation showed good discrimination at the patient level and good calibration at the hospital level, based on the C-index (0.736–0.819) and the concordance correlation coefficient (55.4%–80.3%). Mortality ratios (MRs) showed excellent concordance between administrative and clinical models (97.5% for AMI and 91.6% for PCI). Exclusion of transfers and hospital stays ≤ 1 day did not affect in-hospital mortality prediction in sensitivity analyses, as shown by MR concordance (80.9%–85.4%). Models were used to develop a benchmarking system to compare in-hospital mortality rates of European hospitals with similar characteristics. Conclusions: The developed system, based on the EURHOBOP models, is a simple and reliable tool to compare in-hospital mortality rates between European hospitals in AMI and PCI. Highlights: First international models to estimate in-hospital mortality in AMI and PCI. EURHOBOP models take into account the country, and hospital and patient characteristics. EURHOBOP models allow comparison of in-hospital mortality rates of European hospitals. Administrative and clinical models showed excellent concordance. Exclusion of patient transfers and short hospital stays did not bias predictions.